Metal-Chelation and Biological Activity - Singh, T.K.; Kumar, Ashok (Asian Journal of Chemistry, 2010)
Importance of chelation of multidentate donors with biologically important metal ions has been emphasized in this work. As metal ions involve practically in phases of biological activity, hence this work throws light on useful information for elucidating the various types of mechanism in biological systems. Thus chelate compounds of the general formula (ML)2L1 where M = Na, K, Mg and Ca; L = deprotonated organic acids like lactate and oxalate ions L´= o-carboxyl-bis-benzene-azo-resorcinol and o-nltro-bis-benzene- azo-resorcinol have been synthesised and studied to develop innovative strategies for preparing improved and better complexes in the light of chelate hypothesis.